1976
DOI: 10.1159/000459905
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Fetal Age and Weight from Radiographie Skull Diameters in the Rhesus Monkey

Abstract: In utero radiographic measurements of the skull of a rhesus monkey fetus provide estimates of conceptual age and body weight with about a 6% and 15% error of estimate, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The surgical insult of feto‐maternal system by serial uterotomies did not effect the normal course of pregnancy or the fetus itself. The body weight as well as the skeletal age of our fetal population were comparable to previously reported data [2, 17, 20, 21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The surgical insult of feto‐maternal system by serial uterotomies did not effect the normal course of pregnancy or the fetus itself. The body weight as well as the skeletal age of our fetal population were comparable to previously reported data [2, 17, 20, 21].…”
Section: Discussionsupporting
confidence: 90%
“…The pioneering work of Todd in 1937 [19] resulted in establishment of growth standards of reference for child postnatal development [4, 15]. These fundamental human data stimulated many studies of skeletal development in other species including nonhuman primates [1–3, 5, 7, 13, 14, 18].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this significant acceleration of growth, great similarities were observed in the mode of bone maturation and sequence of ossification in the hand of the M. mulatta and in the human wrist (7, 9, 15, 26, 28, 29, 35). The pioneering work of Van Wagenen and her associates in the late fifties, and more recent studies (1, 3, 4, 6, 1012, 14, 24) carried out on nonhuman primates, indicated that the best criterion for age estimation is appendicular bone maturation. The ossification and fusion of carpal and metacarpal bones prove to be among the most accurate criteria.…”
Section: Discussionmentioning
confidence: 99%